PENINGKATAN LITERASI BENCANA HIDROMETEOROLOGI DALAM MEMBENTUK GENERASI MUDA SADAR LINGKUNGAN DI SMAN 17 PADANG - Eri Stiyanto; Wiliya Wiliya; Nurfaijah Nurfaijah; Ronny Eka Putra; Suhendrik Hanwar (Jurnal Edukasi Pengabdian Masyarakat, 2026)
The technical understanding of the younger generation regarding hydrometeorological disaster mitigation remains low despite their high concern for the climate crisis. The Aie Pacah area in Padang has a high flood risk due to land conversion, which peaked during the massive flood in November 2025. Students of SMAN 17 Padang in this area are both a vulnerable group and future policy makers. This Community Service (PkM) program aims to improve students' disaster literacy through interactive visual education, including water cycle animations and land cover satellite imagery. Evaluation was measured using a Pre-Test and Post-Test. Data analysis of 30 participants using the Paired Sample T-Test showed a significant increase in understanding (Sig. 0,000 < 0,05) with an average margin increase of 30,70 points. Furthermore, the N-Gain Score test reached 0,722 (high category), proving that this digital visual education method is effective. This activity successfully corrected students' perceptions that floods are often triggered by human actions, providing them with a basic foundation to support Disaster Risk Reduction (DRR) policies in the future.